Acidified Feedings in Preterm Infants: A Historical and Physiological Perspective - Barrett-Reis, Bridget; Shakeel, Fauzia; Dennis, Laura; Baggs, Geraldine; Masor, Marc L. (American Journal of Perinatology, 2022)
The use of acidified milk for feeding infants has a long, interesting history that appears to have developed from the use of buttermilk in Holland as early as the late 19th century for feeding infants with diarrhea. Physicians in the early 20th century assumed that the observed benefits were from buttermilk's acidity leading to the practice of acidifying infant formula. The historical and physiological perspective on the use of acidified infant formula is now especially relevant with the emergence of an acidified liquid human milk fortifier for preterm infants. Here, we review that history, with a deeper dive into the contemporary research on the use of acidified human milk fortifiers, the consequences for preterm infants, and the underlying physiological mechanisms.Key Points
Keywords: acidified feedings; human milk fortifier; infant formula; premature infant